A maturing civil society in China? The role of knowledge and professionalization in the development of NGOs. (March 2017) - Hsu, Jennifer Y. J.; Hasmath, Reza
This article suggests that Chinese NGOs do not have the conviction that they are part of an epistemic community in mainland China. Interviews conducted in four cities, Chongqing, Kunming, Nanjing and Shanghai, suggest that this can be attributed to a lack of set standards and professionalization governing their sector of operation. Further, the study finds that Chinese NGOs do not see knowledge production as their primary role within their organizational development life cycle. This may indicate a varying path towards the maturation of civil society in China, whereby Chinese NGOs do not conform to the organizational development process as outlined in extant NGO literature.